Processing interaction protocols in parallel: a logic programming implementation for robotic soccer - Tucat, Mariano (2005)
In this paper we analyze different forms of processing in parallel multi-agent interaction protocols. These protocols will be oriented to a robotic soccer domain with autonomous mobile robots. We will also show how to implement them in an extended logic programming framework. We will explore different situations in which the interaction between agents plays an important role, specially requirements, queries and proposals. Requirements arise when an agent asks another one to execute a specific action. A query is used when an agent wants to know certain information that another agent may have. Finally, proposals arise when an agent wants to synchronize the execution of an action with another agent. We will show one way of implementing these different types of interaction in a specific domain, such as the E-League. The E-League is a robot competition in which two teams of four robots play soccer. The robotic soccer has drawn much attention in the area of multi-agent system research and development. This complex and challenging application domain is useful in the evaluation of different kinds of developments that have been carried out in the field of mobile robotic.